2018
DOI: 10.1111/chd.12691
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamically significant patent ductus arteriosus and the development of bronchopulmonary dysplasia

Abstract: Patent ductus arteriosus (PDA) is prevalent in premature newborns and has been linked to the development of bronchopulmonary dysplasia (BPD), a serious pulmonary complication of premature birth. Although a causal relationship has not been proven, the link is greatest among infants born at lower gestational age who are treated with mechanical ventilation in the presence of a large ductal shunt. Despite strong association in epidemiological studies, treatment of a patent ductus arteriosus has not been shown to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 46 publications
(75 reference statements)
1
26
0
3
Order By: Relevance
“…Persistent patent ductus arteriosus (PDA) in premature infants has been known to be associated with increased mortality and morbidities including bronchopulmonary dysplasia (BPD), and necrotizing enterocolitis (NEC) (1-3); however, there is minimal evidence to support their causal relationship (3)(4)(5). Although it is traditional to manage PDA with nonsteroidal anti-inflammatory agents such as indomethacin, ibuprofen and recently acetaminophen (6), and/or surgical ligation, definite evidence supporting the benefits of these therapies over the conservative non-intervention approach is lacking (7)(8)(9), and they may even be associated with adverse effects (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Persistent patent ductus arteriosus (PDA) in premature infants has been known to be associated with increased mortality and morbidities including bronchopulmonary dysplasia (BPD), and necrotizing enterocolitis (NEC) (1-3); however, there is minimal evidence to support their causal relationship (3)(4)(5). Although it is traditional to manage PDA with nonsteroidal anti-inflammatory agents such as indomethacin, ibuprofen and recently acetaminophen (6), and/or surgical ligation, definite evidence supporting the benefits of these therapies over the conservative non-intervention approach is lacking (7)(8)(9), and they may even be associated with adverse effects (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…A hemodynamically relevant PDA has been associated with pulmonary edema and respiratory compromise has been associated with a resultant higher incidence of BPD. Excessive pulmonary blood flow via the pulmonary vascular bed results in an interrupted lung structure similar to the characteristic BPD changes in immature infants with extremely low birth weight (33). Therefore, a more stable hemodynamics with less PDA could explain the significant reduction in morbidity of BPD in the MISAs group in the subgroup analysis.…”
Section: Discussionmentioning
confidence: 94%
“…Prolonged mechanical ventilation could be also a condition that may have increased the risk of BPD in enrolled newborns affected by hs-PDA. It has been well described by Willis et al that prolonged mechanical ventilation in preterm newborns can determine alveolar simpli cation leading to increased likely to develop BPD [31]. Epidemiological studies demonstrated a strong association between the presence of a PDA and the development of BPD [31].…”
Section: Discussionmentioning
confidence: 97%